PCDD/Fs and heavy metals in the vicinity of landfill used for MSWI fly ash disposal: Pollutant distribution and environmental impact assessment. (1st November 2022) - Lin, Xiaoqing; Ma, Yunfeng; Chen, Tong; Wang, Lei; Takaoka, Masaki; Pan, Shuping; Zhang, Hao; Wu, Angjian; Li, Xiaodong; Yan, Jianhua
Abstract: This study focused on the syngenetic control of polychlorinated-ρ-dibenzodioxins and dibenzofurans (PCDD/Fs) and heavy metals by field stabilization/solidification (S/S) treatment for municipal solid waste incineration fly ash (MSWIFA) and multi-step leachate treatment. Modified European Community Bureau of Reference (BCR) speciation analysis and risk assessment code (RAC) revealed the medium environment risk of Cd and Mn, indicating the necessity of S/S treatment for MSWIFA. S/S treatment significantly declined the mass/toxic concentrations of PCDD/Fs (i.e., from 7.21 to 4.25 μg/kg; from 0.32 to 0.20 μg I-TEQ/kg) and heavy metals in MSWIFA due to chemical fixation and dilution effect. The S/S mechanism of sodium dimethyldithiocarbamate (SDD) and cement was decreasing heavy metals in the mild acid-soluble fraction to reduce their mobility and bioavailability. Oxidation treatment of leachate reduced the PCDD/F concentration from 49.10 to 28.71 pg/L (i.e., from 1.60 to 0.98 pg I-TEQ/L) by suspension absorption or NaClO oxidation decomposition, whereas a so-called "memory effect" phenomena in the subsequent procedures (adsorption, press filtration, flocculating settling, slurry separation, and carbon filtration) increased it back to 38.60 pg/L (1.66 pg I-TEQ/L). Moreover, the multi-step leachate treatment also effectively reduced the concentrations of heavy metals to 1–4 orders of magnitude lower than the national emission standards. Furthermore, the PCDD/Fs and heavy metals in other multiple media (soil, landfill leachate, groundwater, and river water) and their spatial distribution characteristics site were also investigated. No evidence showed any influence of the landfill on the surrounding liquid media. The slightly higher concentration of PCDD/Fs in the soil samples was ascribed to other waste management processes (transportation and unloading) or other local source (hazardous incineration plant). Therefore, proper management of landfills and leachate has a negligible effect on the surrounding environment. Graphical abstract: Image 1 Highlights: S/S treatment reduced the emission of PCDD/Fs and heavy metals from MSWIFA. S/S mechanism was reducing mobility and bioavailability of heavy metals in MSWIFA. Multi-step leachate treatment synergistically reduced PCDD/Fs and heavy metals. PCDD/Fs have "memory effect" during the oxidation process of leachate. Proper management of landfills and leachate lessened environmental impacts of ash.